Distributions of Nursing Student’s Problems with Student Centered Learning Method - Andriany, Megah (Nurse Media Journal of Nursing, 2014)
Purpose: Student centered learning (SCL) method is a new approach in Indonesia in which students have to more proactive in achieving competencies. A nursing school in Semarang, Indonesia has applied this method since 2006. Many students’ achievements were obtained from local, national, and regional level. However, several concerns also came up with this method. This study aims to identify students’ problems with SCL methods from 1st to 4th year grades. Methods: Research design was a descriptive quantitative by conducting survey based on the domains and categories from a qualitative study. The questionnaire has been tested the validity and reliability. The researcher kept the items do not valid since they are significant to explore those crucial problems. Univariate analysis was done to measure the problem percentage in each grade. The investigator described each category in quantitative analysis tables. Results: The results showed that the problem percentages found in the early year almost similar with others. Conclusion: This recommends that it needs learning system improvement from life skill competence arrangements, learning scenario design, and tutor’s capacity enhancement.